Responding to desire to die statements from patients with advanced disease: recommendations for health professionals - Hudson, P.; Schofield, P.; Kelly, B.; Hudson, R.; Street, A.; O'Connor, M.; Kristjanson, Linda; Ashby, M.; Aranda, S. (Sage Science Press (UK), 2006)
Responding to desire to die statements from patients with advanced disease: recommendations for health professionsals.It is not uncommon for patients with advanced incurable disease to express a desire to hasten their death. Health professionals may struggle to determine whether a 'desire to die' statement (DTDS) is about a request for hastened death, a sign of psychosocial distress, or merely a passing comment that is not intended to be heard literally as a death wish. Given the lack of guidelines to assist health professionals with this issue, we have prepared multidisciplinary recommendations for responding to DTDS, underpinned by key principles of therapeutic communication and a systematic review of empirical literature. Where the relevant literature was lacking, the recommendations were drafted by the authors (clinicians and/or academics from the following disciplines: nursing, medicine, psychiatry, psychology, sociology, aged care and theology), based on their expert opinion. Multiple drafts of the recommendations were circulated to the authors for refinement until consensus was reached. Strategies for advancing the evidence base for the maturation of guidelines in this area are offered.